Functional role of p35srj, a novel p300/CBP binding protein, during transactivation by HIF-1 - Bhattacharya, Shoumo (Cold Spring Harbor Laboratory Press, 1999)
Recruitment of p300/CBP by the hypoxia-inducible factor, HIF-1, is essential for the transcriptional response to hypoxia and requires an interaction between the p300/CBP CH1 region and HIF-1α. A new p300-CH1 interacting protein, p35srj, has been identified and cloned. p35srj is an alternatively spliced isoform of MRG1, a human protein of unknown function. Virtually all endogenous p35srj is bound to p300/CBP in vivo, and it inhibits HIF-1 transactivation by blocking the HIF-1α/p300 CH1 interaction. p35srj did not affect transactivation by transcription factors that bind p300/CBP outside the CH1 region. Endogenous p35srj is up-regulated markedly by the HIF-1 activators hypoxia or deferoxamine, suggesting that it could operate in a negative-feedback loop. In keeping with this notion, a p300 CH1 mutant domain, defective in HIF-1 but not p35srj binding, enhanced endogenous HIF-1 function. In hypoxic cells, p35srj may regulate HIF-1 transactivation by controlling access of HIF-1α to p300/CBP, and may keep a significant portion of p300/CBP available for interaction with other transcription factors by partially sequestering and functionally compartmentalizing cellular p300/CBP.